Plastic Waste Utilization of Biaxially Oriented Polypropylene (BOPP) as a Substitute Material for Making Paving Blocks - Muhammad Rafani; Iin Arianti; Nurul Fitriani; Wattini Wattini; Nizar Nizar (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This research explores the potential of using Biaxially Oriented Polypropylene (BOPP) plastic waste in the production of paving blocks. BOPP, a common plastic in packaging, is known for its durability and environmental impact. To investigate its suitability, paving blocks with varying BOPP compositions (40%, 45%, 50%, 55%, and 60%) were created and tested for compressive strength and water absorption. The results indicate that a 50% BOPP composition yielded the best performance, meeting the strength requirements for parking lots. While increasing BOPP content also increased water absorption, it remained within acceptable limits. This research demonstrates the potential of BOPP as a sustainable construction material, reducing plastic waste and contributing to a greener future. The findings provide valuable insights into the utilization of recycled materials in construction, offering a solution to both environmental pollution and the demand for durable, cost-effective building materials.